The Adaptor Protein Swiprosin-1/EFhd2 Is Dispensable for Platelet Function in Mice - Morowski, Martina (Public Library of Science, 2014)
BACKGROUND: Platelets are anuclear cell fragments derived from bone marrow megakaryocytes that safeguard vascular integrity, but may also cause pathological vessel occlusion. Reorganizations of the platelet cytoskeleton and agonist-induced intracellular Ca(2+)-mobilization are crucial for platelet hemostatic function. EF-hand domain containing 2 (EFhd2, Swiprosin-1) is a Ca(2+)-binding cytoskeletal adaptor protein involved in actin remodeling in different cell types, but its function in platelets is unknown. OBJECTIVE: Based on the described functions of EFhd2 in immune cells, we tested the hypothesis that EFhd2 is a crucial adaptor protein for platelet function acting as a regulator of Ca(2+)-mobilization and cytoskeletal rearrangements. METHODS AND RESULTS: We generated EFhd2-deficient mice and analyzed their platelets in vitro and in vivo. Efhd2(-/-) mice displayed normal platelet count and size, exhibited an unaltered in vivo life span and showed normal Ca(2+)-mobilization and activation/aggregation responses to classic agonists. Interestingly, upon stimulation of the immunoreceptor tyrosine-based activation motif-coupled receptor glycoprotein (GP) VI, Efhd2(-/-) platelets showed a slightly increased coagulant activity. Furthermore, absence of EFhd2 had no significant impact on integrin-mediated clot retraction, actomyosin rearrangements and spreading of activated platelets on fibrinogen. In vivo EFhd2-deficiency resulted in unaltered hemostatic function and unaffected arterial thrombus formation. CONCLUSION: These results show that EFhd2 is not essential for platelet function in mice indicating that other cytoskeletal adaptors may functionally compensate its loss.